A Zebrafish Model of Neurotoxicity by Binge-Like Methamphetamine Exposure - Bedrossiantz, Juliette; Bellot, Marina; Dominguez-García, Pol; Faria, Melissa; Prats, Eva; Gómez-Canela, Cristian; López-Arnau, Raul; Escubedo, Elena; Raldúa, Demetrio (Frontiers in Pharmacology, 2021)
Hyperthermia is a common confounding factor for assessing the neurotoxic effects of methamphetamine (METH) in mammalian models. The development of new models of methamphetamine neurotoxicity using vertebrate poikilothermic animals should allow to overcome this problem. The aim of the present study was to develop a zebrafish model of neurotoxicity by binge-like methamphetamine exposure. After an initial testing, zebrafish was exposed to 40 mg/L of METH for 48h, and the effects on the brain monoaminergic profile, locomotor, anxiety-like and social behaviors as well as on the expression of key genes of the catecholaminergic system were determined. A concentration- and time-dependent decrease in the brain levels of dopamine (DA), norepinephrine (NE) and serotonin (5-HT) was found in METH-exposed fish. A significant hyperactivity was found during the first hour of exposure followed 3h after by a positive geotaxis and negative scototaxis in the novel tank and in the light/dark paradigm, respectively. Moreover, the behavioral phenotype in the treated fish was consistent with social isolation. At transcriptional level, th1 and slc18a2 (vmat2) exhibited a significant increase after 3h of exposure, whereas the expression of gfap, a marker of astroglial response to neuronal injury, was strongly increased after 48h exposure. However, no evidences of oxidative stress were found in the brain of the treated fish. Altogether, this study demonstrates the suitability of the adult zebrafish as a model of METH-induced neurotoxicity and provides more information about the biochemical and behavioral consequences of METH abuse.